Adapting Lean methods to facilitate stakeholder engagement and co-design in healthcare. (28th January 2020) - Smith, Iain; Hicks, Chris; McGovern, Tom
Abstract : Quality improvement approaches drawn from industry can go beyond traditional concepts of value and deliver improvements in healthcare services, argue Iain Smith and colleagues